2011
DOI: 10.1068/p6837
|View full text |Cite
|
Sign up to set email alerts
|

Vection in Depth during Consistent and Inconsistent Multisensory Stimulation

Abstract: We examined vection induced during physical or simulated head oscillation along either the horizontal or depth axis. In the first two experiments, during active conditions, subjects viewed radial-flow displays which simulated viewpoint oscillation that was either in-phase or out-of-phase with their own tracked head movements. In passive conditions, stationary subjects viewed playbacks of displays generated in earlier active conditions. A third control, experiment was also conducted where physical and simulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Because their screens are small and close to the eyes, screen positions and orientations relative to the eyes become important (e.g., incorrect interocular separations and/or HMD alignment on the head can lead to visual display artefacts). Different types of software projection errors are also possible, such as exaggerating/minimising the visual consequences of the tracked head motions [53], applying the compensatory visual motion along the wrong axis [54] or in the wrong direction [3,55], and accidently switching the left and the right eyes views of a stereo 3D simulation [56]. All of these display calibration and software errors would be more salient when the head is moving -and thus their potential for inducing cybersickness would also be expected to increase.…”
Section: Relationship Between Head-movements and Cybersickness In Hmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because their screens are small and close to the eyes, screen positions and orientations relative to the eyes become important (e.g., incorrect interocular separations and/or HMD alignment on the head can lead to visual display artefacts). Different types of software projection errors are also possible, such as exaggerating/minimising the visual consequences of the tracked head motions [53], applying the compensatory visual motion along the wrong axis [54] or in the wrong direction [3,55], and accidently switching the left and the right eyes views of a stereo 3D simulation [56]. All of these display calibration and software errors would be more salient when the head is moving -and thus their potential for inducing cybersickness would also be expected to increase.…”
Section: Relationship Between Head-movements and Cybersickness In Hmdsmentioning
confidence: 99%
“…Four SSQ scores were calculated for each subject using methods and weighting factors outlined in [53]: a total SSQ score and three sub-scores (nausea, oculomotor symptoms, and disorientation). In each case pre-scores were subtracted from the post-scores.…”
Section: Cybersicknessmentioning
confidence: 99%
“…A number of recent studies suggest that such visually-mediated self-motion perceptions can be facilitated by physically moving the observer in a manner consistent with the visual simulation (Berger et al 2010;Wong and Frost 1981;Wright, 2009;Bubka and Bonato 2010) or by incorporating active head motions of the observer directly into the self-motion display (Ash et al 2011a;Ash et al 2011b). 1 When taken together, such findings suggest that consistent multisensory stimulation may produce a more compelling overall experience of self-motion than visual self-motion stimulation alone.…”
Section: Introductionmentioning
confidence: 79%
“…However, several recent studies appear to show that visually induced vection is surprisingly tolerant to a number of so-called "sensory conflict" situations Ash et al 2011a;Ash et al 2011b;Palmisano 2008, 2010;Palmisano et al 2011). For example, we have found that compelling vection can still be induced even when visual and non-visual self-motion stimulations are 180 degrees out-of-phase or indicate self-motion along completely different axes .…”
Section: Experience?mentioning
confidence: 99%
“…Recently, Ash et al (2011) found that vection in depth could be increased by subjects actively moving their heads from left-and-right while viewing radial flow. Consistent with the findings of the current experiment, congruent (in-phase) horizontal head-and-display movements increased vection more than incongruent (180º out-of-phase) horizontal head-and-display movements.…”
mentioning
confidence: 99%